The effects of adding zirconium oxide Micro-particles to high impact polymethyl methacrylate on some mechanical properties - Elgtlawi, Dr.Mohamed; Saleh, Dr.Amel M; O Elaogal, Mr.Omar (Libyan Journal of Dentistry, 2020)
Aim: The purpose of this study was to investigate the transverse strength and impact strength of high impact heat-cured Poly (Methyl Methacrylate) (PMMA) reinforced with zirconium oxide particles (ZrO2). Materials and Methods: A total of sixty specimens were fabricated for each test. The denture base materials evaluated in this study were divided equally into three groups (A), (B) and (C) for each test. group (A) control group, unmodified high impact heat cured (PMMA). Group (B) ‎&‎ ‎(C) high impact heat cured (PMMA) reinforced with 5% ‎&‎ ‎10% (ZrO2) powder respectively by volume. The transverse strength was measured using the three point bending test. The impact strength was measured using the Chrapy impact tester. The micro-structural study of the fracture surfaces of test specimens ‎was performed using Scanning Electron Microscope. Results: Statistical analysis were conducted on the data obtained from the experiments using one way analysis of variance(ANOVA).Both ‎the transverse strength and impact strength of high impact heat cured PMMA reinforced with ‎treated ZrO2 particles were superior to the unreinforced high impact heat cured PMMA. However, the improvement in transverse strength was not directly proportional with the amount of filler particles. Scanning electron micrographs showed the degree of bonding between the filler particles and PMMA matrix.